Developing new cassava varieties: tools, techniques and strategies - Ceballos, H.; Morante, Nelson; Calle, Fernando; Lenis Calderon, Jorge Iván; Salazar Erazo, Sandra Milena (Burleigh Dodds Science Publishing Limited, 2017)
The significance of cassava as a crop in tropical countries means that developing improved varieties is key to the sustainability of cassava production. This chapter examines how understanding the utilization of cassava can inform breeding objectives for developing improved varieties of cassava. It addresses the ways through which cassava can be bred and selected to resist common pests and diseases and examines the selection criteria used for breeding. The chapter analyses in detail the correlation between phenotypic characteristics and traits of cassava, as well as including a discussion of the relevance of breeding value. The chapter suggests a number of potential future trends in research in this area.